Endogenous indeterminacy and volatility of asset prices under ambiguity. Issue 3 (18th September 2013) - Mandler, Michael
Abstract : If agents are ambiguity‐averse and can invest in productive assets, asset prices can robustly exhibit indeterminacy in the markets that open after the productive investment has been launched. For indeterminacy to occur, the aggregate supply of goods must appear in precise configurations, but the investment levels that generate these supplies arise systematically. That indeterminacy arises only at a knife‐edge set of aggregate supplies allows for a simple explanation of the volatility of asset prices: small changes in supplies necessarily lead to a large price response.